C11 DAE RESPONDER APP IN PIACENZA: AN INTEGRATED RESCUE NETWORK AGAINST CARDIAC ARREST USING THE TECHNOLOGY AVAILABLE FOR DAE RESPONDERS CITIZENS. (18th May 2022) - Aschieri, D; Pelizzoni, V; Rossi, E; Nani, S; Bertocchi, S; Bersani, E; Ferraro, S; Pisati, M; Losi, G
Abstract: Introduction: Early Defibrillation is the most effective method for resuscitation in patients with out of hospital cardiac arrest(OHCA). The presence of shockable rhythm is an important determinant of survival, therefore, the implementation of systems that increase the likelihood of immediate CPR and rapid defibrillation are vital to improving survival. To this end, in 2017 the DAE REsponder APP (ADR) was developed to alert the trained citizens nearest to the scene and direct them to the closest DAE. Aim: To evaluate the performance of this application in terms of number of interventions and number of patients saved. Methods: Since 2014, the Emilia Romagna region created a regional portal dedicated to the OHCA the AED REspondER emergency, in which each province registered the automated external defibrillators (AEDs), indicating their geolocation and accessibility. From this system was developed the ADR, which can be used by every citizen through their smartphone. ADR has several functions: alerting the DR citizens closest to the victim, possibility to choose whether to intervene or not, in case of acceptance, navigation to the place and to the AED closer. Results: In Piacenza 1046 AEDs have been placed and 1212 people are registered as DR.From 2018, 525 blue codes have been activated (out of a regional total of 4457) and 80560 notifications have been sent to DRs: in 145 cases (27.62%)the intervention was accepted, in 19 cases DR arrived before 118 and in 12 cases the AED was applied (63.16%) with 7(55%) patients survived. Conclusion: The ADR could be considered an effective method to deliver an immediate CPR and increase the chance of survival in case of OHCA.